1991
DOI: 10.1093/clinchem/37.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Interferences in current methods for measurements of creatinine

Abstract: We measured the interference of carbonyl compounds, drugs, and other substances in human serum on the determination of creatinine by the two-point, fixed-time kinetic modification of the Jaffé reaction as well as by four enzymatic methods. We added known concentrations of the interfering substances to a solution of creatinine in water. For bilirubin, we used both pooled normal sera with added bilirubin and icteric patient sera. The magnitude of interferences varies widely from method to method. Carbonyl compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(82 citation statements)
references
References 0 publications
2
77
0
3
Order By: Relevance
“…This is in accordance with earlier laboratory studies in which b-hydroxybutyrate did not cause interference in the alkaline picrate method [2,4,11]. One laboratory study showed that each mmol L 21 of glucose caused a positive error of 0.3±0.4 mmol L 21 of creatinine, which is similar to the estimation in our multivariate analysis [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in accordance with earlier laboratory studies in which b-hydroxybutyrate did not cause interference in the alkaline picrate method [2,4,11]. One laboratory study showed that each mmol L 21 of glucose caused a positive error of 0.3±0.4 mmol L 21 of creatinine, which is similar to the estimation in our multivariate analysis [23].…”
Section: Discussionsupporting
confidence: 92%
“…At presentation of DKA, the range of acetoacetate concentration was 1.3±5.1 and 3.6±3.9 mmol L 21 , respectively, in the two mentioned examples. The interference was greater than expected from laboratory studies using spiked' samples up to 20 mmol L 21 acetoacetate and from our own in vitro experiment [17,18,20,23]. This can be due to acetone in the patient sample.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A bilirubin stock solution of 400 mg/dL was prepared by dissolving 40 mg of bilirubin powder (Sigma-Aldrich, St. Louis, MO, USA) in 10 mL of 0.1 M sodium hydroxide (NaOH). 5,6 Serial dilutions of the bilirubin stock solution with 0.1 M NaOH were mixed with constant proportions of sera (1 part bilirubin solution + 9 parts serum) to create bilirubin concentrations between 1 and 40 mg/dL (17 and 684 lmol/L) in the first set of spiked sera, and between 4 and 35 mg/dL (68 and 598 lmol/L) in the second set of spiked sera. The first set of spiked sera was assayed to document the interference; the second set was assayed to confirm findings of the first set, and to explore the reason for the interference.…”
Section: Bilirubin Stock Solution and Preparing Icteric Seramentioning
confidence: 99%
“…Plasma creatinine concentration was successively determined on the Vitros analyzer and the Olympus AU2700 analyzer, using three reagents in the same assay: Olympus-Jaffe´and two enzymatic commercial kitsFCrea Plus and Enzymatic Creatinine. The Jaffe´kinetic method is known to be subject to several interferences and poor specificity (1)(2)(3)(4). In addition, the commonly used Jaffe´and modified Jaffe´reaction methods systematically overestimated creatinine by 20% compared to enzymatic methods (5).…”
Section: Introductionmentioning
confidence: 99%